ANALISIS PRAKTEK SHARENTING SEBAGAI UPAYA MEMENUHI KEBUTUHAN SELF ESTEEM PADA IBU MUDA - Maulidiyah, Ummi Masrufah; arumsari, andini dwi (Universitas Narotama, 2024)
The research was conducted to understand how the need for appreciation or self-esteem is a factor for young mothers in practicing sharenting and to find out how the phenomenon of sharenting itself generally occurs in various countries in the world. Sharenting itself is a combination of two words,